Implementation of Differentiated Learning in Improving Problem-solving Skills in Collaborative Projects Based on Science and Technology - Desy Aprima; Sasmita Sari (Inovasi Matematika)
The urgency of this research is that the implementation of differentiated learning is important because it encourages the development of critical problem-solving skills at the Elementary School level. Through this approach, each student can receive learning that is appropriate to their ability level, allowing them to actively participate in collaborative science and technology projects. The purpose of this study was to determine the implementation of differentiated learning in improving problem-solving skills in collaborative science and technology-based projects for elementary school students. The method used in this study is a mixed method with a Sequential Exploratory design. Sequential Explanatory research is a type of quantitative-qualitative research design that combines both approaches in two consecutive phases. The first phase is the collection and analysis of quantitative data, followed by the collection and analysis of qualitative data to explain the findings of the first phase. The population used in this study were all 5th grade students of Rejodadi Elementary School. The sample used in this study was 29 students of Rejodadi Elementary School and 1 teacher. The research instruments used in this study were test instruments, observation instruments, and interview instruments. The data collection techniques used in this study were tests with objective test types, observations to observe the learning process directly and interviews to dig deeper into the views of the research subjects. The data analysis techniques in the study were descriptive quantitative data analysis and descriptive qualitative data analysis. The results of the study in the implementation of differentiated learning in elementary school students' collaborative science and technology projects showed that teachers succeeded in designing projects that accommodated students' needs well with a differentiated learning approach, through the division of roles based on individual abilities, which allowed each student to contribute according to their understanding of the cognitive level accompanied by science and technology-based project learning, and the results showed that the ability to understand problems got the highest results for students compared to the ability to plan problems, solve problems, and recheck. By designing science and technology projects that are more responsive to students' needs, it is hoped that students' involvement and problem-solving abilities can increase, as well as encourage more effective and comprehensive learning in the classroom.